Pergeseran Kategori dalam Penerjemahan Klausa Nominal Bahasa Inggris ke Bahasa Indonesia pada Novel Third Girl - Tapilatu, Terweline; Lewaherilla, August (DINAMIS, 2024)
The translation of English noun clauses into Indonesian can result in a range of potential outcomes, some of which may be unexpected. This qualitative research focuses on the category shift variations that occur when translating English noun clauses into Indonesian and the strategies for achieving equivalence between the two texts. The data were collected from Agatha Christie's novel Third Girl and its translation "Gadis Ketiga" and analyzed using the content analysis method. The findings show that two category shifts occurred, i.e. structure shifts and unit shifts. The structure shifts that occurred include the shift of a clause element subject-predicate to predicate-subject, the shift of a phrase structure to a clause structure in a noun clause, the shift from active voice into passive voice, the shift of an affirmative clause to a negative clause, the shift of a noun clause to a simple sentence, the shift of an affirmative sentence to an interrogative sentence, and the shift of a noun clause to an adverbial clause. The unit shifts found are the shifts of a noun clause to a noun phrase, a noun clause to a prepositional phrase, and a noun clause to a verb phrase. The equivalence is achieved by employing functional equivalents and by attending to the meaning of the sentence as a whole, rather than focusing solely on the meaning of the noun clause. These shifts have resulted in changes in sentence structure, changes in syntactic category and function, changes in sentence type, changes in rank, changes in type of question, and shifts in meaning. This research will enrich the study of applied linguistics, particularly regarding the translation from English to Indonesian.